Relationship between student engagement and academic performance - Çali, Megi; Lazimi, Loren; Ippoliti, Beatrice Maria Luna (Institute of Advanced Engineering and Science, 2024)
This research aims to investigate the impact of student engagement on academic performance. Using a sample of 196 students from the University of Tirana, Faculty of Economics, we used multiple regression to assess the effect of behavioral engagement, cognitive engagement, and emotional engagement on student’s performance. The results of the engagement model created using three constructs show a correlation between overall student engagement and academic performance. In this study, we identified that behavioral engagement was the only significant factor for academic performance, while the two other factors, namely, emotional and cognitive engagement were not significant factors for students’ academic performance. We also identified that there was a significant difference between bachelor and master students as well as their year of study. The coefficient for “bachelor and first class” is negative and significant. However, there are no substantial differences between working students and non-working students or their gender in the relationship between engagement and academic performance. Our results provide additional empirical evidence for the higher education institution, teachers, parents and peers and some pointers for policy making. Increasing the engagement of students brings benefits for all involved stakeholders.